2011
DOI: 10.1017/s1460396911000422
|View full text |Cite
|
Sign up to set email alerts
|

Recording a patient diet over the radical course of radiotherapy for prostate cancer using a diet diary: a feasibility study

Abstract: Aims: To obtain an estimate of dietary fibre and fluid intake in Australian men undergoing prostate radiotherapy and to establish feasibility and patient compliance with recording normal diet without intervention during the radical course of radiotherapy.Methods: Eleven participants were enrolled and treated with 74–78 Gray (Gy) to the prostate over 8 weeks. Participants were instructed to record a diary of their food and fluid intake and bowel motions for the duration of treatment. Treating radiation therapis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…We were pleased to read that other groups are exploring the feasibility of detailed self-recording of dietary intake in patients receiving long-course radiotherapy for prostate cancer. This has particular relevance in view of the continued interest in strategies to minimise rectal deformation and thus reduce prostate movement during radiotherapy planning and treatment 1 . We completely agree with the authors’ finding that previous studies, which have explored dietary interventions (primarily anti-flatulent diets), have lacked information on patient compliance 2 4 .…”
supporting
confidence: 77%
See 1 more Smart Citation
“…We were pleased to read that other groups are exploring the feasibility of detailed self-recording of dietary intake in patients receiving long-course radiotherapy for prostate cancer. This has particular relevance in view of the continued interest in strategies to minimise rectal deformation and thus reduce prostate movement during radiotherapy planning and treatment 1 . We completely agree with the authors’ finding that previous studies, which have explored dietary interventions (primarily anti-flatulent diets), have lacked information on patient compliance 2 4 .…”
supporting
confidence: 77%
“…This has particular relevance in view of the continued interest in strategies to minimise rectal deformation and thus reduce prostate movement during radiotherapy planning and treatment. 1 We completely agree with the authors' finding that previous studies, which have explored dietary interventions (primarily anti-flatulent diets), have lacked information on patient compliance. [2][3][4] Thus, in the one study, which failed to show a statistically significant difference in inter-fraction prostate motion, 2 and in the two studies, in which worse outcomes were observed in terms of increased prostate displacement, 3,4 it is impossible to know whether the outcomes result from a true lack of efficacy or indeed adverse effects of the diet alone.…”
supporting
confidence: 71%
“…Therefore, the importance of establishing an individual's baseline dietary intake, providing a target that can be realistically achieved, and the resources to monitor and analyze this should not be underestimated. 27,30 A significant reduction in volume and percentage change in rectal volume during treatment was found using probiotics 10 (Table 4). However, while probiotics are easy to administer, the optimal dose, bacterial strains used, and their effect on microbiota through radiation therapy treatment have yet to be clearly established.…”
Section: Discussionmentioning
confidence: 95%